Transimpersonal constructions in Lithuanian: towards the emergence of Split Intransitivity - Piccini, Silvia (Baltistica, 2015)
Transimpersonal constructions have recently attracted the attention of many scholars, especially in the field of functional typology, as they have been proven to play an important role in the rise of Split Intransitive patterns in languages. In the light of these recent advances, this article evaluates several constructions regarded as “impersonal” in Lithuanian reference grammars, with the aim of reinterpreting them as transimpersonal.The investigation was carried out mainly from a synchronic perspective by focusing on Modern standard Lithuanian, although, where appropriate, comparisons with data drawn from Old Lithuanian and especially from dialects were also taken into account. The analysis was based on verbs denoting physical states, which can participate in a variety of syntactic constructions according to their meaning. The different behaviour shown in synchrony by these experiencer verbs can be projected into a diachronic perspective. As a result,it has been possible to shine a light on the various stages in the process of reanalysis as it gradually moves in the direction of the emergence of patterns of Split Intransitivity. Some verbs seem to have advanced further along the path of reanalysis; however, genuine patterns of Split Intransitivity seem not to have emerged yet. In fact, the subject-status of the experiential arguments licensed by the verbs analysed still remains problematic when viewed from a syntactic standpoint.
Keywords: Lithuanian; syntax; Transimpersonal constructions; Split Intransitivity; Psychological verbs